Improving Thermal Comfort and Indoor Air Quality through Minimal Interventions in Office Buildings. (March 2017) - Khatami, Narguess; Hashemi, Arman
Abstract: High internal heat gain and slow reaction of occupants to overheating have been identified as major contributors to risk of thermal discomfort in offices. This paper reports on the findings of a research programme which investigates the impacts of reducing internal heat gain and introducing automated ventilation strategies into lightweight open plan offices. It is aimed to developed intervention strategies with minimum disruption to occupants in order to improve energy performance thermal comfort and indoor air quality (IAQ). A case study building was selected and dynamic thermal simulation was conducted to test the performance of proposed strategies. The results reveal that tested strategies reduced the risk of overheating and poor IAQ by 64% and 90%, respectively. The energy consumption was also reduced by 2.1% for the best case scenario.